Pengaruh Penambahan Sari Wortel (Daucus carrota L.) terhadap Karakteristik Marshmallow - Rofianatul Jannah, Novia; Ekawati, I Gusti Ayu; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p07, 2023)
Marshmallows, a chewy candy made from sugar, water, flavoring, and gelatin, are traditionally manufactured using artificial coloring. To enhance their safety for consumption, there's a shift towards natural ingredients as replacements for artificial dyes. Among these ingredients, carrots stand out as a potential source of natural dye. This study aims to investigate the optimal concentration of carrot puree addition to marshmallow production for desired characteristics. A Complete Randomized Design was employed, involving six carrot juice addition levels: P1 (50% carrot juice), P2 (60% carrot juice), P3 (70% carrot juice), P4 (80% carrot juice), P5 (90% carrot juice), and P6 (100% carrot juice). Each treatment was replicated three times, resulting in 18 experimental units. The collected data were subjected to analysis of variance using the SPSS program at a significance level of ?=5%. Post hoc analysis was conducted using Duncan's Multiple Range Test if significant effects were observed. The findings highlighted the substantial impact of carrot juice addition on various marshmallow attributes, including ash and moisture content, reduction sugar content, beta carotene content, color and texture analysis, as well as sensory characteristics like taste and overall acceptance. The optimal treatment emerged as 70% carrot juice (P3), exhibiting key attributes such as moisture content (18.45%), ash content (0.39%), reduction sugar content (10.93%), total beta carotene (254.70 mg/100g), L value* (64), a* (31.40), and b* (49.10). The marshmallow's chewiness texture was rated at 2.10 N, displaying a preferred orange color, desired chewy texture, favored carrot flavor, distinct carrot aroma, and overall acceptance were liked.